Review On Statistics (Second Published) - Tay, Choo Chuan; Sakidin, Hamzah; Sek, Yong Wee; Law, Check Yee (Penerbit Universiti Teknikal Malaysia Melaka, 2011)
One of the most challenging aspects of mathematics learning is to give students suitable examples and exercises which can improve their understanding. This book is designed to familiarize the student with the form of questions asked in Statistics. The topics are based on the syllabus of Statistics teaching in UTeM. The material in this book will cover questions and answers for: Data Description and Numerical Measures Probability Discrete Random Variables Continuous Random Variables Sampling Distributions Estimation Hypothesis Testing Estimation and Hypothesis Testing for Two Populations Correlation and Simple Linear Regression. An excellent student must have an initiative to learn before being taught by lecturers. By using this book, students can be more prepared before attending a tutorial session. The examples are presented in a sequence of steps with full details so that students can follow systematically.